The Effect Of Hedonic Shopping Motivation And Flash Sale Program In Tiktok Live Shopping On The Impulsive Buying Behavior Of Generation Z - Syifa Az Zahra; Nor Lailla (UNIVERSITAS PAKUAN, 2025)
The purpose of this study is to (1) To determine the effect of Hedonic Shopping Motivation on Impulsive Buying. (2) To determine the effect of Flash Sale on Impulsive Buying. (3) To determine the effect of Flash Sale on Hedonic Shopping Motivation. This study uses a descriptive quantitative method and the population in this study is the community in DKI Jakarta who use the TikTok application. The sample used uses the Non Probability formula with a total sample of 300. The data is processed using the Partial Least Square (PLS) method. From the results of the analysis, it was found that Impulsive Buying was 56.6% influenced by Hedonic Shopping Motivation and Flash Sale.